PENERAPAN METODE PROBLEM BASED LEARNING DAN MEDIA GAMBAR DALAM PEMBELAJARAN MEMBACA CERITA - ASRI MUSANDI WARAULIA (Universitas PGRI Madiun, 2016)
This is qualitative description research about implementation of Problem Based Learning method and image media in learning Indonesian with reading material story. The purpose of this study, are: 1) describe the application of learning model Problem Based Learning and media images in reading story; 2) describe the involvement of the student, and 3) describe the ability to read stories fifth grade students of SDN Sambirejo 3. The subjects of this research were students and teachers Indonesian class V SDN Sambirejo 3 2015/2016 school year. Data collected through observation, interview, test, and document analysis. The validity of the data used two techniques, the triangulation of methods and triangulation of data sources. Comparative critical analysis technique is a technique of data analysis in this study. Application method of Problem Based Learning and Media Images in reading stories had some problems. These obstacles include: (1) the teacher has not been accustomed to in the application of methods, (2) the students still were not fully explore the capabilities of learning, and (3) time management was less appropriate. From learning activities that have been carried out, there was an excess obtained among other things, teachers were able to use the media images properly and the students also enjoyed using the learning with media images, as well as student activity developed well in the classroom. The final value of learning is as below the average value of 77.2 with the percentage of completeness 85% or 17 students. Based on the finding of research, it can be concluded that the implementation of Problem Based Learning method and the use of media images can make students active in learning and reading skills increased